Effects of human tissue acoustic properties, abdominal wall shape, and respiratory motion on ultrasound-mediated hyperthermia for targeted drug delivery to pancreatic tumors - Gray, M; Spiers, L; Coussios, C (Taylor and Francis Group, 2022)
Background